3D Reconstruction of Traditional Handicrafts Based on Binocular Vision. (26th June 2022) - Qin, Yi; Xu, Zhipeng
Abstract : As an indispensable and essential material part of China's traditional culture, traditional handicrafts have played a more important role in modern life. It is not only the crystallization of the wisdom of the Chinese people of all nationalities but also an excellent platform to display China's long-standing culture. However, the protection and reconstruction of traditional handicrafts are relatively lagging. To realize the reconstruction of traditional handicrafts, this paper proposes an improved AD-Census stereo matching algorithm of a binocular measurement system for object positioning and three-dimensional reconstruction. Methods based on the principle of binocular vision measurement include firstly, histogram equalization, adaptive threshold Canny edge extraction, and expansion are used for image preprocessing; Secondly, the calibration method is used to complete camera calibration, remove camera distortion through stereo correction, and improve the AD-Census stereo matching algorithm based on gradient division of weak texture and edge area. Finally, the parallax map generated by the improved algorithm is used to realize three-dimensional reconstruction. The experimental results show that this method can control the error standard deviation within 0.5 mm, can realize the reconstruction of traditional handicrafts, have high accuracy, and can be widely used in practice.